10-year trends and inpatient outcomes of gastrointestinal angiodysplasia with bleeding in the United States: National Inpatient Sample, 2011 to 2020. Issue 3 (4th May 2023) - Rasheed, Waqas; Abu-Hassan, Falah
Abstract: Gastrointestinal angiodysplasia (GIAD) is the presence of aberrant blood vessels in the gastrointestinal (GI) tract that can lead to GI bleeding. There has been an increase in the incidence of GI angiodysplasia, partly due to the availability of better diagnostic techniques. The cecum is known as the most common site for GIAD; therefore, GIAD is considered a frequent cause of lower GI bleeding. Studies have shown an increasing incidence of GIAD in the upper GI tract and jejunum. No population-based studies exist on inpatient outcomes of GIAD-bleeding (GIADB) in recent years, and no prior studies have compared the inpatient outcomes of upper vs lower GIADB. We identified 321, 559 weighted hospitalizations and found a 32% increase in GIADB-related hospitalizations from 2011 to 2020. There were more hospitalizations for upper (57.38%) than lower GIADB (42.62%), indicating GIADB is an important cause of upper GI bleeding as well. No statistically significant difference in mortality was found between upper and lower GIADB cohorts; however, lower GIADB was associated with a 0.2-day longer length of stay (95% confidence interval 0.09–0.30, P   <  0.001) and $3857 higher mean inpatient cost (95% confidence interval $2422–$5291, P   <  0.001).